A Educação Física no ensino noturno e o aluno trabalhador: como lidar? - Pedroso, Antulho Rosa (1996)
The brazilian educational system shouls similar problems in both noctumal and diumal tums. However, in the noctumal education these problems are much more complex and difficult to be solved. Noctumal schools receive students whose majority must work to help the home budget. Consequently, these students have less time and vigor to dedicate to the didactics activities than the diumal students. This work investigates the pedagogical practice of the physical education related to working-students of public noctumal schools. Three schools from the state network of Minas Gerais, Brazil, were choosen to be visited and observed, where informal surveys and questionaries were undertaken to verify the relationship between teachers and students. The results suggests lack of appropriate knoledge and refinement among teachers dealing with their working-students while proposing and planing general activities. The link between the school and work environment of these students does not take place.